2013
DOI: 10.1155/2013/436589
|View full text |Cite
|
Sign up to set email alerts
|

The Importance and Perspective of Magnetic Resonance Imaging in the Evaluation of Endometriosis

Abstract: MR imaging is becoming increasingly important in the assessment of patients with endometriosis. Its multiplanar capabilities and superior soft tissue contrast are particularly useful in the detection of deep infiltrating endometriotic implants. Endometriosis, defined as the presence of endometrial glands and stroma outside the endometrium, is among the most common gynaecological disorders affecting women in their reproductive age. The diagnosis and evaluation of the extension of endometriosis are difficult onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…Owing to its higher costs relative to other imaging modalities, magnetic resonance imaging (MRI) is less frequently applied for the assessment of endometriosis. However, MRI is useful in cases where ultrasonography findings are equivocal and in carefully selected, high‐risk patients (e.g., those with extensive pelvic adhesions of suspected ureteral involvement) . Nonetheless, this method is helpful for cases where ultrasonographic findings are equivocal or for use among carefully selected high‐risk patients such as those with extensive pelvic adhesions or suspected ureteral involvement .…”
Section: Imaging Studies As An Adjunct To Clinical Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its higher costs relative to other imaging modalities, magnetic resonance imaging (MRI) is less frequently applied for the assessment of endometriosis. However, MRI is useful in cases where ultrasonography findings are equivocal and in carefully selected, high‐risk patients (e.g., those with extensive pelvic adhesions of suspected ureteral involvement) . Nonetheless, this method is helpful for cases where ultrasonographic findings are equivocal or for use among carefully selected high‐risk patients such as those with extensive pelvic adhesions or suspected ureteral involvement .…”
Section: Imaging Studies As An Adjunct To Clinical Diagnosismentioning
confidence: 99%
“…However, MRI is useful in cases where ultrasonography findings are equivocal and in carefully selected, high‐risk patients (e.g., those with extensive pelvic adhesions of suspected ureteral involvement) . Nonetheless, this method is helpful for cases where ultrasonographic findings are equivocal or for use among carefully selected high‐risk patients such as those with extensive pelvic adhesions or suspected ureteral involvement . One advantage of MRI is that interpretation of the results is less operator‐dependent compared with TVUS .…”
Section: Imaging Studies As An Adjunct To Clinical Diagnosismentioning
confidence: 99%
“…This alone has a fundamental role when counseling patients regarding treatment modalities (12). Many studies have suggested transvaginal sonography (TVS) as a good method to identify DPE (12)(13)(14)(15)(16) since this technique allows extensive exploration of the pelvis and is usually well accepted and widely available (4,15).…”
mentioning
confidence: 99%
“…Moreover, the choice regarding one method rather than another remains ''empirical'' or based on personal experience (9,(13)(14)(15)(16)(19)(20)(21)(22)(23). Therefore, the aim of this study was to collate all available data and to compare the efficacy of each method to the others to identify the most effective technique to assist clinicians in the diagnosis, assessment, and localization of DPE.…”
mentioning
confidence: 99%
“…MRT yra laikomas tiksliausiu tyrimo metodu priešope-raciniam giliosios endometriozės židinių įvertinimui [17]. Intraveninės kontrastinės medžiagos panaudojimas nepadeda diferencijuoti endometriozės židinių nuo aplinkinių fibromuskulinių struktūrų, o kontrastinės medžiagos susikaupimas parametriumo audiniuose arba smulkiose kraujagyslėse gali būti klaidingai palaikytas endometriozės židiniu.…”
Section: Rezultatų Aptarimasunclassified